ENGLISH JUNIOR HIGH SCHOOL TEACHERS’ AND STUDENTS’ PERSPECTIVES OF DIFFERENTIATED INSTRUCTION PRACTICES IN KURIKULUM MERDEKA - Astuti, Yulia Fitri; Syafei, Muh; Suryani, Fitri Budi (SIMPLE: International Journal of English Education, 2023)
This study proposes to explore English Junior High School teachers’ and students’ perspectives of differentiated instruction practices in Kurikulum Merdeka. The study conducted a descriptive qualitative approach. Three teachers and 3 classes of each grade of Junior High School students were selected to become participants in this study. The data were gathered through questionnaires, semi-structured interviews, classroom observations, and document analysis. The result of this study revealed that all teachers and most of the students had positive perspectives on the use of Differentiated Instruction in the classes. That was indicated from their positive thoughts on their planning and implementation that Differentiated instruction became an effective and engaging learning practice in the classroom. The teachers planned the lesson with different stages but with the same topic. The teachers are evaluated as good practitioners for students in practicing Differentiated Instruction. And most of the students had positive feedback on their experiences and found when the teachers implemented differentiated instruction strategies in their classes, they could overcome their learning difficulties. All this result leads to the alignment of the differentiated instruction practices that should be implemented in any classroom activities